2017
DOI: 10.15570/actaapa.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical minimally invasive rhinoplasty: tips and tricks from the perspective of a dermatologist

Abstract: Introduction: Rhinoplasty is one of the most common aesthetic procedures performed by plastic surgeons all over the world. In recent years, a non-surgical nose job has become the preferred option for most patients and specialists. Minimally invasive techniques already result in high satisfaction rates. Moreover, patients do not need anesthesia and there is no post-operative recovery period. Methods: Between January 2016 and January 2017, 35 patients (33 female, 2 male) that had undergone nonsurgical rhinoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…An attempt was made to distinguish any unpublished studies and to contact the authors of published studies for additional information. The studies excluded have been shown in Table 2, 14,28‐38 along with the reasons for their exclusion.…”
Section: Methodsmentioning
confidence: 99%
“…An attempt was made to distinguish any unpublished studies and to contact the authors of published studies for additional information. The studies excluded have been shown in Table 2, 14,28‐38 along with the reasons for their exclusion.…”
Section: Methodsmentioning
confidence: 99%
“…En el estudio de Yordanov y colaboradores (48) se encontró una alta satisfacción de los pacientes a los seis y 12 meses de aplicar AH. En el estudio de Sahan y colaboradores (49) se utilizó una escala de 0 a 5 (5 = muy satisfecho). En 32 de los 35 pacientes, el puntaje fue 5, dos pacientes calificaron con 4 y un paciente con 3.…”
Section: Efectividad De Los Rellenosunclassified
“…Descriptions of a wide array of NSR techniques that utilize various fillers are available in the literature, but none to the authors' knowledge are specific to PMMAcollagen gel. [23][24][25][26][27][28][29][30][31] Due to its unique properties and longevity, there is a need to define optimal technique and appropriate patient selection and share advanced injection skills for NSR. Here, we provide an overview of how the author selects and treats NSR patients using PMMA-collagen gel.…”
Section: Takeawaysmentioning
confidence: 99%